2011
DOI: 10.1074/jbc.m111.292961
|View full text |Cite
|
Sign up to set email alerts
|

The Deubiquitinase CYLD Targets Smad7 Protein to Regulate Transforming Growth Factor β (TGF-β) Signaling and the Development of Regulatory T Cells

Abstract: Background: CYLD is a deubiquitinating enzyme (DUB) that hydrolyzes Lys-63-linked polyubiquitin chains that are attached covalently to cellular proteins.Results: CYLD knock-out mice have increased numbers of regulatory T cells (Tregs) in peripheral lymphoid organs but not in the thymus.Conclusion: CYLD regulates lysine 63-linked ubiquitination of Smad7 to control the development of peripheral Tregs.Significance: TGF-β signaling in T cells is regulated by lysine 63-Linked ubiquitination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 35 publications
2
57
0
2
Order By: Relevance
“…Studies using knockout mice revealed a role for CYLD in T cell biology (67)(68)(69)(70). In these studies, the absence of CYLD resulted in reduced accumulation of mature thymocytes and peripheral T lymphocytes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies using knockout mice revealed a role for CYLD in T cell biology (67)(68)(69)(70). In these studies, the absence of CYLD resulted in reduced accumulation of mature thymocytes and peripheral T lymphocytes.…”
Section: Discussionmentioning
confidence: 91%
“…In these studies, the absence of CYLD resulted in reduced accumulation of mature thymocytes and peripheral T lymphocytes. In addition, the differentiation of the CD4 ϩ T lymphocytes into T regulatory cell subsets was halted (67)(68)(69)(70). Cleavage of CYLD by the cellular paracaspase MALT1 was necessary for proper activation of CD4 ϩ T cells in response to T cell receptor stimulation (57).…”
Section: Discussionmentioning
confidence: 99%
“…The USP family member CYLD (cylindromatosis), plays a role in the generation of Tregs. In response to TGF-β signaling, K63-linked polyubiquitylation of Smad7 results in stabilized Smad7 which activates TAK1, increases binding of AP-1 to the foxp3 promoter, and increases Foxp3 transcription 122 . CYLD opposes this process by removing K63 chains on Smad7.…”
Section: Regulatory T Cells (Tregs)mentioning
confidence: 99%
“…The crystal structure of the USP domain and results from in vitro deubiquitylation assays have demonstrated that CYLD has lysine-63 (K63)-linked polyubiquitin-chain-specific endodeubiquitylase activity (Komander et al, 2008(Komander et al, , 2009Sato et al, 2015). A series of studies has found that CYLD regulates multiple signaling pathways, including nuclear factor-кB (NF-кB), Wnt/β-catenin, c-Jun Nterminal kinase (JNK), p38 mitogen-activated protein kinase ( p38 MAPK), transforming growth factor-β (TGF-β), Hippo and Notch signaling Lim et al, 2012;Massoumi, 2010;Rajan et al, 2014;Welte et al, 2014;Zhao et al, 2011) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%